HUBUNGAN ANTARA KARAKTER DEMOKRASI SISWA DENGAN MODEL PEMBELAJARAN PEMECAHAN MASALAH - Gurbani, Yash; Nawahdani, Ahmad Mansur; Azzahra, Miftahul Zannah (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Democratic character is very important for students to have, one of the efforts to improve students' democratic character is to apply a problem-solving learning model. This study aims to answer the research question, namely how is the relationship between democratic character variables and solving learning models in high school students in Jambi and Heidelberg in physics subjects. The method used in this research is a mixture of quantitative and qualitative methods. The results of the study are the correlation test which states that the relationship with the data results is less than 0.05, which means that there is a relationship between the two variables. The conclusion from this study is that there is a relationship between students' democratic character and students' problem-solving learning models. The novelty of this study is at the same time a differentiator from previous research, namely testing whether there is a relationship between students' democratic character and problem-solving learning models. The limitation of this research is that it only describes the democratic character based on the school, but it has not been carried out based on gender in each school. Researchers suggest conducting further research to compare the characteristics of democracy and problem-solving models with an analysis based on gender.